SURG-05. Α5Β1 INTEGRIN TARGETING LIPOSOME DELIVERY OF MIR-603 SUPPRESSED GLIOBLASTOMA STEM CELL STATE AND ENHANCED RADIATION SENSITIVITY. (12th November 2021) - Shabana, Ahmed; Xu, Beibei; Shneiderman, Zachary; Ma, Jun; kokkoli, efrosini; Chen, Clark
Abstract: INTRODUCTION: Despite the potential for clinical efficacy, therapeutic delivery of microRNAs (miRNA) remains a major translational barrier. Here, we explore a surgery mediated polyethylenimine (PEI)/liposome-based strategy for the delivery of miR-603, a master regulatory miRNA that suppresses glioblastoma stem cell state by simultaneous down-regulation of insulin-like growth factor 1 (IGF1) and IGF1 receptor (IGF1R). METHODS: miR-603 was complexed with PEI, a cationic polymer designed to facilitate miRNA from the endolysosomal compartment. The miR-603/PEI complex was encapsulated into liposomes decorated with polyethylene glycol (PEG) and PR_b, a fibronectin-mimetic peptide that specifically targets the α5β1 integrin that is overexpressed in glioblastoma. RESULTS: Patient-derived glioblastoma cells internalized PR_b coated liposomes but not the non-coated liposomes. The internalization of PR_b liposomes encapsulating miR-603/PEI was associated with orders of magnitude increase in intra-cellular miR-603 levels and decreased IGF1 and IGF1R mRNA/protein levels. Moreover, treatment of glioblastoma cells with the PR_b liposomes encapsulating miR-603/PEI showed altered morphology and decreased expression of stem cell marker, suggesting the treated cells have exited the cancer stem cell state. Finally, treatment of the PR_b liposomes encapsulating miR-603/PEI sensitized glioblastoma cells to ionizing radiation (IR) in patient-derived glioblastoma cells. These results were not observed in liposomes missing the PR_b peptide, PEI, or miR-603. CONCLUSION: These results suggest that intra-tumoral injection of PR_b functionalized PEGylated liposomes encapsulating miR-603/PEI complexes hold promise as a strategy for glioblastomas therapy. A first-in-human trial is currently underway to test this strategy.